Kedudukan Saksi Sebagai Syarat Nikah dalam Hukum Islam - Asri Sabrina Koto; Siti Aini (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This article examines marriage law as a form of uniformity and legal certainty. However, there are still differing views among Islamic scholars (fuqaha) regarding the position of witnesses in marriage. In light of this, the author is interested in discussing the role of marriage witnesses as one of the requirements for marriage according to the four fiqh schools of thought. This research employs a literature review method by collecting primary and secondary data from books, journals, and other legal regulations. The findings show that, according to the four fiqh schools, a marriage witness is an individual who clearly and certainly knows about the marriage event and is ready to provide evidence that can be held accountable if required by either party regarding the occurrence of the marriage. In the context of legal regulations, a marriage witness is recognized as one of the pillars of marriage, based on the view of the Shafi’i school. Two witnesses are the minimum requirement for marriage, and the purpose of having witnesses is to prevent the emergence of negative issues in society related to extramarital relationships. The presence of marriage witnesses also affirms the rights that arise after the marriage contract, such as the right to consultation, maintenance rights, and inheritance rights.